Universal anomaly of dynamics at phase transition points induced by Pancharatnam-Berry phase. (1st May 2023) - Zhang, Jia-Yuan; Yin, Xia; Liu, Ming-Yu; Zhao, Jize; Ding, Yang; Chang, Jun
Abstract: Dynamical anomalies are often observed near both the continuous and first-order phase transition points. We propose that the universal anomalies could originate from the geometric phase effects. A Pancharatnam-Berry phase is accumulated continuously in quantum states with the variation of tuning parameters. Phase transitions are supposed to induce an abrupt shift of the geometric phase. In our multi-level quantum model, the quantum interference induced by the geometric phase could prolong or shorten the relaxation times of excited states at phase transition points, which agrees with the experiments, models under sudden quenches and our semi-classical model. Furthermore, we find that by setting a phase shift of π, the excited state could be decoupled from the ground state by quantum cancellation so that the relaxation time even could diverge to infinity. Our work introduces the geometric phase to the study of conventional phase transitions as well as quantum phase transition, and could substantially extend the dephasing time of qubits for quantum computing.